Is There a Paradox Between the Evaluation and Recruitment of Public Servant in Greece? - Myrotis, Panagiotis; Xagorari, Virginia (HAPSc Policy Briefs Series, 2025)
The following Policy Brief attempts to present the new institution of evaluation in the public sector in Greece and its relationship with the procedures for recruiting procedure of higher education public servants. It seems that there is an evaluation system with basic principles and two-way evaluation procedures. On the contrary, in what has to do with recruitment, it seems that both delay and confusion have prevailed. While the procedures are quite close to the evaluation of existing personnel, there is a confusion that requires political interventions. In the conclusion of the study, an attempt is made to propose policies regarding the pathologies identified.